2006
DOI: 10.1055/s-2006-926491
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Motor Activity in Response to Physiological Meals of Different Chemical Composition in Man

Abstract: Meals disrupt the interdigestive pattern of small bowel motor activity and convert it into the more irregular postprandial pattern. Previous animal studies suggest that the duration of and contractile activity within the postprandial period depend on the chemical composition of a meal. It is not clear whether this is also true for man. In 8 healthy volunteers I investigated how physiological and isocaloric meals of different chemical composition affect small bowel motor activity. Volunteers underwent two separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Attempts to characterize this motor activity during the fed period have yielded contradictory results [3][4][5][6][7] that may be related to the species studied, composition of test meals, route of administration, and caloric load.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to characterize this motor activity during the fed period have yielded contradictory results [3][4][5][6][7] that may be related to the species studied, composition of test meals, route of administration, and caloric load.…”
Section: Introductionmentioning
confidence: 99%
“…Duration of X-ray exposure was also documented. In England, tubes were placed under fluoroscopic control [6, 7], whereas in Germany the position of the catheter was controlled using a combination of sonography and pH-metry [8]. …”
Section: Methodsmentioning
confidence: 99%
“…In the sonography/pH-metry group 18 tubes were placed in 10 volunteers. Most volunteers underwent repeat investigations, due to the comparative nature of the study protocols [6,7,8]. None of the volunteers participated in both study groups, and the two volunteer groups were not significantly different.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult pigs, however, the MMC is interrupted when the animal is fed discrete, large meals, but not by ad libitum feeding with the same diet (Bueno and Ruckebusch, 1976). Other research has shown that the caloric load regulates the characteristics of the amplitude of contraction and the duration of the intestinal postprandial pattern in adult pigs (Gregory et al, 1986), dogs (Schang et al, 1978;Schmid et al, 1992) as well as in adult humans (Schönfeld et al, 1998). Furthermore, it was demonstrated in adult dogs that during enteral infusion of low caloric load, MMC persisted, apart from a lengthening of phase II and resulting increase in duration of the MMC cycles; only higher caloric load caused complete disruption of the MMC and appearance of postprandial pattern (Defilippi, 2003).…”
Section: Introductionmentioning
confidence: 99%